Approach of utilizing Artemisia herbs to treat covid-19 - Hmed Ben-Nasr; Riadh Badraoui (Universidade de São Paulo, 2023)
Abstract Huge plethora of studies pointed out the importance of several Artemisia herb molecules as treatment for many diseases. Among these natural substances, some molecules are known to counteract fever, inflammation, blood clotting and oxidative stress. Furthermore, they are dotted with activities against different strains of viruses including the SARS-coronaviruses. For these beneficial properties, these medicinal herbs are deemed as a potential candidate for covid-19 pandemic.